2013
DOI: 10.1371/journal.pone.0061516
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of the Effect of Type 2 Diabetes Mellitus on Subgingival Plaque Microbiota by High-Throughput 16S rDNA Pyrosequencing

Abstract: Diabetes mellitus is a major risk factor for chronic periodontitis. We investigated the effects of type 2 diabetes on the subgingival plaque bacterial composition by applying culture-independent 16S rDNA sequencing to periodontal bacteria isolated from four groups of volunteers: non-diabetic subjects without periodontitis, non-diabetic subjects with periodontitis, type 2 diabetic patients without periodontitis, and type 2 diabetic patients with periodontitis. A total of 71,373 high-quality sequences were produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
106
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 100 publications
(120 citation statements)
references
References 79 publications
12
106
1
1
Order By: Relevance
“…In the present study, the frequency of periodontal sites harboring A. actinomycetemcomitans, P. gingivalis, T. forsythia, P. intermedia and C. rectus (Cr) was statistically similar between the groups. Our results corroborate with those found by Field et al 7 , Sardi et al 8 and Yuan et al 28 and differ from other studies [29][30][31][32] . We focused on subgingival sites with periodontal disease, specifically deep pockets, for both groups, also reported by the majority of these studies.…”
Section: Discussionsupporting
confidence: 91%
“…In the present study, the frequency of periodontal sites harboring A. actinomycetemcomitans, P. gingivalis, T. forsythia, P. intermedia and C. rectus (Cr) was statistically similar between the groups. Our results corroborate with those found by Field et al 7 , Sardi et al 8 and Yuan et al 28 and differ from other studies [29][30][31][32] . We focused on subgingival sites with periodontal disease, specifically deep pockets, for both groups, also reported by the majority of these studies.…”
Section: Discussionsupporting
confidence: 91%
“…To account for the uneven sequencing depth between samples, a normalized procedure was used as previously described (14,15). Differences in the abundance of specific genera between groups (i.e., uninfected vs. untreated, uninfected vs. 1-yr treated, and uninfected vs. 3-yr treated) were analyzed using negative binomial regression models.…”
Section: Data Analysis and Statisticsmentioning
confidence: 99%
“…T2DM has been reported previously and represents a major predisposing factor (4,5,23,24). In a recent report, Zhou et al (25) found that the amount of Actinomyces and Aggregibacter on the gingival microbiota of diabetic patients was significantly higher compared to non-diabetics. CFA pathogenesis is favored by anaerobiosis and a microaerophilic atmosphere.…”
Section: Discussionmentioning
confidence: 82%